2022
DOI: 10.3389/fpubh.2021.781562
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of COVID-19 Vaccine Among Hospital Employees in the Department of Paediatrics, Gynaecology and Obstetrics in the University Hospitals of Geneva, Switzerland

Abstract: Background and AimsCOVID-19 vaccination has been in the spotlight for almost a year now, both within the scientific community and in the general population. The issue of healthcare workers' (HCWs) hesitancy is particularly salient, given that they are at the forefront of the fight against COVID-19. Not only could unvaccinated HCW spread the disease, but HCWs are also critical messengers in building confidence towards COVID-19 vaccines. The goal of this study was to examine the perception of COVID-19 risk and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…This finding is consistent with what has been reported in different countries [26], where hesitant HCWs have been described as having a consistently low severity perception, albeit being one higher than the general population [27]. Moreover, those who thought that a COVID-19 infection could be extremely severe in adults were 12.5 times more likely to have been vaccinated [28]. The expansion of vaccination and greater knowledge about patient management could have an impact on this perception globally, as French HCW have also been reported to exhibit a decrease in perception severity over time [29].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with what has been reported in different countries [26], where hesitant HCWs have been described as having a consistently low severity perception, albeit being one higher than the general population [27]. Moreover, those who thought that a COVID-19 infection could be extremely severe in adults were 12.5 times more likely to have been vaccinated [28]. The expansion of vaccination and greater knowledge about patient management could have an impact on this perception globally, as French HCW have also been reported to exhibit a decrease in perception severity over time [29].…”
Section: Discussionsupporting
confidence: 91%
“…Professional responsibility and physicians' role in vaccinations are strong predictors of immunization behavior. 32 , 33 , 34 , 35 Nurses and healthcare assistants were the professionals with the lowest vaccination uptake in both seasons even though they are on the front line in caring for patients. 34 This hesitancy may be due to poor knowledge about vaccines and vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the need to return to normality was also a reason for greater adherence to vaccination. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain studies, a lower vaccination rate was noted [ 19 ]. However, some research indicated a far greater rate [ 45 , 46 ]. Astrzeneca (53.1%) and Sinopharm (20.7%) were the two most frequently received vaccines in our cohort.…”
Section: Discussionmentioning
confidence: 99%